Watching the Watchers: New Perspectives on Spectatorship, Gaming and Online Media - Taylor, Nicholas; Szablewicz, Marcella; Bowman, Nicholas; Harper, Todd (AoIR Selected Papers of Internet Research, 2013)
Electronic sports (e-sports) represents the configuration of competitive videogaming as spectatorial, professionalized sport, problematizing conventional distinctions between work and leisure, ‘geek’ and ‘jock’ cultures, and crucially, between playing games and watching others play. Much of the scholarship on e-sports has focused primarily on players and player communities involved in the ‘professionalization’ of digital gaming, examining players’ game-based skillsets (Rambusch, Jakobsson & Pargman, 2007), the ways they negotiate the rules, expectations and challenges that come with professional play (Witkowski, 2012), and the formation of gendered subjectivities afforded (and constrained) by the confluence of gaming and sport (Taylor, 2010). Recent work by TL Taylor (2012) and Todd Harper (2010) have begun to extend the study of competitive play beyond players, examining the fundamental role of spectatorship in the social, technological and economic development of e-sports. As TL Taylor points out in Raising the Stakes, the connections between spectatorship and play run deep. While The Wizard, Twin Galaxies, and Starcade may have presented spectatorial gaming as an entertaining, if quirky sideshow, watching others play - whether attending tournaments, bars or arcades in person, or simply watching others in between turns at the controls - has arguably always been an integral, albeit understudied, part of gaming culture (Alloway & Gilbert, 1998; Lin & Sun, 2011; Taylor, 2012). Over the last 15 years, however, the loosely affiliated and often volatile assortment of clans, tournaments and leagues collectively representing the e-sports industry has sought to cultivate a mass online audience for competitive, elite gaming. Recent developments have demonstrated that there is indeed a global audience for e-sports, made possible both by the surging popularity of specific games as well as by the emergence of high definition, live streaming webcasts, and the various viewer practices and business models these make possible. Major League Gaming (MLG), the self-proclaimed “world’s largest e-sports organization”, recently reported 11.7 million “live online viewers” for online, streaming webcasts of MLG’s Pro Circuit tournament play in 2012 (MLG, 2012). The last day of competition of the 2012 Spring Championship, held June 8-10 in Anaheim, CA, which featured the League of Legends and Starcraft 2 finals, drew 2.2 million viewers to MLG’s webcast – more than their total number of unique viewers for all 2010. Over roughly the same period of time, Twitch (http://www.twitch.tv/) has emerged as a highly popular venue to watch live-streaming videogame play, including e-sports. Boasting over 23 million subscribers a month, the platform has not only offered a means for e-sports organizations, teams and individual players to reach potentially massive audiences, but it has served to further enact and legitimate the notion of gaming as something we watch as well as something we do. The recent success of MLG and Twitch, as well as the (related) surging popularity of Starcraft 2 and League of Legends, have seemed to establish e-sports as a legitimate and viable entertainment media industry (Tassi, 2013). At the same time, the short history of professional gaming is marked as much by sudden declines as by sudden success; claims that ‘e-sports has finally arrived’ were heard shortly before the collapse of the longstanding Cyberathlete Professional League (CPL) and the much-touted Championship Gaming Series (CGS) in 2008-2009, for instance (Kane, 2010). Outside of South Korea, where e-sports has had a solid foothold for some time (Jin, 2010), competitive gaming organizations struggle to attract and maintain sponsorship for what is still largely seen, by potential sponsors, as a marketing experiment (Taylor, 2012, p. 146). Adding to this the high “churn” rate of players, games, and tournaments (p. 153); the brevity of players’ careers and the relatively short shelf life of games and gaming platforms means that the constellation of pro-gaming ‘stars’ shifts rapidly. For these reasons, competitive gaming is very much a moving target for researchers: often, by the time a particular community, tournament, or organization is reported on in academic publications, it no longer exists in the same form, if at all. Given this dynamic and unpredictable terrain, one of the central challenges for e-sports researchers is to link accounts of competitive gaming to larger transformations in digital games, social media, and emerging forms of both leisure and labor. Each of the papers on this panel undertakes this project, whether through linking e-sports spectatorship in China to issues of censorship, nationality, and broadcasting, analyzing the fundamental role of spectators in enacting and shaping the psychological and social experiences of play, or exploring changes in the ways spectators have been incorporated into the ‘assemblage’ of North American e-sports broadcasting over the past five years. Collectively, this panel represents an attempt to more productively understand the crucial role that audiences carry out in the ongoing socio-technical transformation of digital play as spectatorial activity.